2012
DOI: 10.14195/2183-203x_35_3
|View full text |Cite
|
Sign up to set email alerts
|

Micro credit and territory: Portugal as a case study

Abstract: This paper studies the relations between micro credit and territory, assuming that micro credit is an important instrument for fighting against poverty and social exclusion. Based on a micro-level database provided by ANDC (Associação Nacional de Direito ao Crédito), a statistical and econometric study has been undertaken in order to identify the territorial idiosyncrasies associated with the employment of micro credit in Portugal. Focusing on the survival of micro credit projects during the period 2006-2009, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Microcredit has gained a greater dimension over the years, transforming into the much wider IJBM 42,4 concept of microfinance, meaning the supply of a whole range of financial and non-financial services to the poor, including microcredit, micro-insurance, micro-savings, training, and others (Cobb et al, 2016;Ferdousi, 2015). Microfinance is considered the most appropriate tool for dealing with credit constraints to overcome poverty and social problems by promoting financial access to the base-of-the-pyramid (BOP) markets, integrating this segment of the population into the economic system, namely by enabling entrepreneurship (Afonso et al, 2011;Bateman and Chang, 2012;Kent and Dacin, 2013;Wulandari and Kassim, 2016).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Microcredit has gained a greater dimension over the years, transforming into the much wider IJBM 42,4 concept of microfinance, meaning the supply of a whole range of financial and non-financial services to the poor, including microcredit, micro-insurance, micro-savings, training, and others (Cobb et al, 2016;Ferdousi, 2015). Microfinance is considered the most appropriate tool for dealing with credit constraints to overcome poverty and social problems by promoting financial access to the base-of-the-pyramid (BOP) markets, integrating this segment of the population into the economic system, namely by enabling entrepreneurship (Afonso et al, 2011;Bateman and Chang, 2012;Kent and Dacin, 2013;Wulandari and Kassim, 2016).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Entrepreneurial activity has indeed been associated with poverty alleviation (Si et al, 2020;Sutter et al, 2019) and, when supported to be opportunity-oriented, it has an important economic role in developing countries (Urbano et al, 2020). Therefore, to reach a double bottom line of financial viability and social impact, MFIs that promote entrepreneurship and self-employment developed around the world (Afonso et al, 2011;Archer and Jones-Christensen, 2011;Bateman and Chang, 2009;Chliova et al, 2015). The debate around the need to add the environmental dimension as an additional objective of the MFIs has started after studies have shown that some of the activities promoted and supported by these institutions are harmful to the environment, such as agricultural activities that use MFIs' funds to purchase pesticides and fertilisers and contribute to deforestation, and hazardous chemical and toxic waste production (Anderson et al, 2002;Archer and Jones-Christensen, 2011).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 2 more Smart Citations